ANALISIS PERMINTAAN KREDIT MODAL KERJA USAHA KECIL DI KOTA PONTIANAK (Studi Kasus Permintaan Modal Kerja Usaha Kecil Sektor Perdagangan dari BMT) - Jumhur . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2009)
One of the problems faced by small business is capitalization difficulty. Thisdifficulty emerges because of various requirements which cannot be fulfilled. Hencealternatively to overcome this legal capital problem they borrow to Lembaga KeuanganMikro/LKM. One of LKM which is enough concern in development of this small businessis BMT. Research aim to identify factors influencing demand probability of smallbusiness working capital credit from BMT and analyses does asset value factor, basicyield, sharing holder ratio and single source rate in other finance companies can predictin significan demand probability of commercial sector small business working capitalcredit from BMT in Pontianak. Testing with logistics regression is obtained by asset totalvariable and single source rate in other finance companies had an effect on significan todemand probability of small business working capital credit from BMT, while advantagefactor per month and sharing holder ratio significan doesn't to small business probabilityborrows circulating capital from BMT at level of significan 5%.Key words: small business, credit, working capital, BMT, probability